RECOGNIZING, APPRECIATING AND PRESERVING WOMEN’S RIGHTS: ISSUES, RATIONALES AND CHALLENGES FOR WOMEN IN FACING SOCIAL RESPONSIBILITY - Irma Wani Othman; Suwaibah Zakaria; Mohd Sohaimi Esa (INTERNATIONAL JOURNAL OF LAW, GOVERNMENT AND COMMUNICATION (IJLGC), 2024)
The discussion in this paper focuses on issues that increase the awareness and understanding of society on the importance of achieving common equality in a fair way to optimize women’s ability to provide a sustainable future for the country. Among issues discussed (i) Career issues halt for highly educated women with families, (ii) The issue of women as victims of domestic violence, (iii) Elimination of gender discrimination in an effort to dignify women, (iv) Confusion over the issue of women’s human rights labelled as a family, community and welfare, and (v) Denial of women’s entrepreneurial potential and leadership credibility in the national political arena. This paper uses secondary sources, such as research results published in journals, scholarly writing, online news sources, and public forums, to employ a qualitative methodology. The results of the study present information regarding (a) Gender discrimination, cultural clashes and community perceptions, (b) Implementation & enforcement of the Domestic Violence Act 1994, (c) Viability of the National Women’s Policy 2009, (d) Strengthening the functions and jurisdictions of the Affairs Unit Woman (EVE). The rationale for preserving women’s rights is for the society to be aware of the importance of women in mobilizing the economy, social, and culture. In addition, the recognition and appreciation of women’s contributions must continue to ensure a more prosperous, peaceful and prosperous future for the country. The direction for the future undertaking should focus on the significance of women’s empowerment in guaranteeing the development of the country which no longer refers solely to economic development but covers development in terms of social, personality and community unity.